Description of a rock-dwelling cichlid that re-invaded the sand substrate in Lake Malaŵi, Africa - Konings, Adrianus F.; Miller, Torin A.; Jr., Jay R. Stauffer (Zootaxa, 2024)
Pseudotropheus Regan had been a catch-all genus for many of the rock-dwelling cichlids of Lake Malaŵi, known as mbuna, for over half a century. Although many of the species previously assigned to this genus have since been allocated to other genera there are still about a dozen species in the genus that do not appear to be closely related to its type species, P. williamsi, but for which no better placement could be found. Pseudotropheus livingstonii (Boulenger) is one such species and the new species described herein appears to be closely related and has for that reason been temporarily assigned to Pseudotropheus. Pseudotropheus likomae n. sp. from Likoma Island can be diagnosed from all other Pseudotropheus spp., by having five or fewer distinct vertical bars below the dorsal fin and two horizontal stripes in mature individuals.